Concrete-Ice Abrasion: Laboratory Studies using a Sawn Concrete Surface - Shamsutdinova, Guzel; Hendriks, Max; Jacobsen, Stefan (Norsk Betongforening, 2017)
Concrete-ice abrasion is a surface degradation mechanism due to ice-structure interaction especially relevant for concrete gravity-based structures in the Arctic offshore. Experiment is the main evaluation method for concrete durability against ice abrasion. The paper presents NTNUs lab facilities and a 4 km concrete-ice abrasion test between a sawn concrete surface with fc cube = 110 MPa and unidirectionally grown fresh water ice. Results demonstrate the load cells response, coefficient of friction and a 0.03 mm/km abrasion rate measured with laser scanner. Further research is discussed. acceptedVersion This is the accepted version of the article.